A cross-sectional mixed methods study protocol to generate learning from patient safety incidents reported from general practice. Issue 12 (1st December 2015) - Carson-Stevens, Andrew; Hibbert, Peter; Avery, Anthony; Butlin, Amy; Carter, Ben; Cooper, Alison; Evans, Huw Prosser; Gibson, Russell; Luff, Donna; Makeham, Meredith; McEnhill, Paul; Panesar, Sukhmeet S; et al.
Abstract : Introduction: Incident reports contain descriptions of errors and harms that occurred during clinical care delivery. Few observational studies have characterised incidents from general practice, and none of these have been from the England and Wales National Reporting and Learning System. This study aims to describe incidents reported from a general practice care setting. Methods and analysis: A general practice patient safety incident classification will be developed to characterise patient safety incidents. A weighted-random sample of 12 500 incidents describing no harm, low harm and moderate harm of patients, and all incidents describing severe harm and death of patients will be classified. Insights from exploratory descriptive statistics and thematic analysis will be combined to identify priority areas for future interventions. Ethics and dissemination: The need for ethical approval was waivered by the Aneurin Bevan University Health Board research risk review committee given the anonymised nature of data (ABHB R&D Ref number: SA/410/13). The authors will submit the results of the study to relevant journals and undertake national and international oral presentations to researchers, clinicians and policymakers.